(untitled) (Orinoquia, 2022)
The predominant swine production systems in the Colombian Orinoquia, which are based on commercial feed, selected breeds, and a high reliance on external inputs, are currently vulnerable due to market prices and agricultural supply volatility.. The strategic use of local resources, adapted to local conditions and highly available, such as creole pig breeds, would be an alternative to increase the competitiveness of regional swine production. The objective was to evaluate growth performance, carcass characteristics and meat quality of crossbred “Casco de Mula” pigs at two slaughter weights managed under a confinement system. The results obtained indicate a competitive growth performance of the crossbreed “Casco de Mula” pigs. Feed conversion of pigs up to 76 kg of body weight was 2.3 at d136 of the finishing period and an average daily gain of 686.8 grams/day. Carcass yield was 77%, and backfat at the 10th rib was 16 mm. In addition, these crossbred pigs generated yields of high-value cuts (loin 4% and leg 24%) similar to those of commercial pigs. The pH and temperature curves, as well as moisture losses of 5%, indicate good meat quality of this crossbreed pigs; no PSE meat characteristics (pale, soft and oxidative) were evident. This racial crossing under the management conditions described is an alternative for pig production that allows the strategic use of genetic and agricultural resources of the Orinoquia, increasing the range of action of Swine production in this region, improving the performance of the “Casco de Mula” pig, with competitive carcass characteristics and meat quality. It will be important to evaluate more aspects of the meat quality that could confer added value and reach differentiated markets.